Timur Lenk’s Military Invasion in Anatolia in 1402-1403 AD - Surya Atta, Rafif Naufal; Jauhari, Najib (JUSPI (Jurnal Sejarah Peradaban Islam), 2024)
This study explains the Timur Lenk’s Military Invasion in Anatolia in 1402 to 1403 AD. Using historical methods, the author uses various written sources. Available sources include books and scientific articles. In this study, the author analyzes the factors of Timur's victory in war, based on the theories of war explained by Sun Tzu. The findings from this research reveal that the situation of the regions in Anatolia, politically experienced changes after the military invasion of Timur Lenk, especially after Timur's victory over the Ottoman Empire under the leadership of Sultan Bayazid I in the battle of Ankara on July 20, 1402. The situation of the regions in Anatolia experienced changes, both in terms of government, which was shown by the return to power of the government of small kingdoms in Anatolia, after previously being under the rule of Bayazid I, the struggle for power between Ottoman Turkish princes after the capture of Bayazid I in Samarkand, and the destruction of Izmir in 1403 due to Timur Lenk's politically motivated invasion.